Macroeconomic Influence on Zakat Growth in 34 Indonesian Provinces - Muslih, Bayu Setiaji (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2024)
This study aims to evaluate the effect of macroeconomic variables on zakat growth in Indonesia using the Random Effect Model (REM). The data used is panel data from 2019-2023. The variables analyzed include Gross Regional Income (GRDP) per capita, Regency/City Minimum Wage (MSW), percentage of Muslim population, and Covid-19 pandemic. The regression results show that GRDP per capita and UMK do not have significant influence on zakat growth, with p-value greater than 0.05. In contrast, the percentage of Muslim population has a significant influence on zakat growth, with p-value <0.05, which indicates that the higher the percentage of Muslim population, the greater the potential for zakat growth. In addition, the condition of the Covid-19 pandemic does not show a significant influence on zakat revenue. This study found that demographic factors, especially the proportion of Muslim population, have more influence on zakat collection than economic indicators such as GRDP per capita and UMK. The findings of this study can be used to evaluate the performance of zakat collection by zakat management organizations in Indonesia and by policymakers in order to improve the realization of zakat collection more optimally.